Relationship between Moral Sensitivity and Moral Reasoning with Moral Courage in Nursing Students - Atefeh Babaei; Maryam Bagheri; Mohsen Shahriari (Iranian Journal of Nursing and Midwifery Research)
Background: Nursing students required to be prepared to face ethical problems in their future workplace. Solving moral dilemmas requires the implementation of moral decisions, which necessitates significant moral courage. Moral sensitivity and moral reasoning can play a key role in the emergence of morally courageous behavior. The aim of this study was to investigate the relationship between moral sensitivity and moral reasoning with moral courage in nursing students. Materials and Methods: This was a cross-sectional study. The participants consisted of 296 nursing students of Isfahan University of Medical Sciences, Iran, in 2021, which selected through the census method. Data were collected using the Persian versions of the Moral Sensitivity and Sekerka’s Moral Courage questionnaires and Nursing Dilemma Test. Data were analyzed by SPSS software (v. 25.0) using descriptive and analytical statistical methods (t-test, ANOVA, Pearson correlation, and regression analysis). Results: A total of 296 nursing students participated in this study. The results showed no significant correlation between moral sensitivity and moral courage (r = 0.04, p = 0.41); however, a significant positive correlation was observed between moral reasoning and moral courage (r = 0.19, p < 0.05). The results of multiple regression analysis showed that moral reasoning was the only predictor of moral courage in nursing students (p < 0.05). Conclusions: oral reasoning ability played a more significant role in developing moral courage than moral sensitivity. Tracking the sensitivity, reasoning, and moral courage status during education can reveal valuable information on the process of moral practice formation in nurses.